Mashitah, Sabdin and M Ridhuan Tony Lim (2010) Student’s Perspective on Factor Influencing Them in Understanding and Practicing the Sunnah of Prophet Muhammad S.A.W. International Journal of Basic & Applied Sciences IJBAS-IJENS Vol:10 Issue: 02 pp 61-69. ISSN: 2077-1223 - Sabdin, Mashitah (International Journal of Basic & Applied Sciences IJBAS-IJENS, 2010)
Abstract-This study is an attempt to identify secondary school students’ views concerning their understanding and practice of Sunnah of the Prophet Muhammad S.A.W., specifically the factors that influence students in secondary religious schools in Malaysia in order to understand and practice the Sunnah in their daily life. The samples for this study consisted of 576 students from four secondary religious schools selected from four states in Malaysia. The study adopts a survey technique via questionnaires to collect data. The questionnaire was analyzed based on the Likert Scale. The findings revealed that the students’ attitude is the most prominent factor that may influence them in understanding and practice of Sunnah of Prophet Muhammad S.A.W. (mean=18.14) besides other factors like Parents’ role (mean=17.42), Teachers (mea=15.22) and Syllabus (mean=13.49). The outcome of this study could assist teachers, schools administrators, students and the Ministry of Education of Malaysia in equipping students with Islamic teachings. This research is also hoped to enrich the Hadith literature and Hadith study in Malaysia. Thus a fresh draft can be drawn to upgrade the Hadith studies in the curriculum to benefit a new generation of students in Hadith studies.